2013
DOI: 10.1093/humrep/det409
|View full text |Cite
|
Sign up to set email alerts
|

Barcode tagging of human oocytes and embryos to prevent mix-ups in assisted reproduction technologies

Abstract: This study was supported by the Sociedad Española de Fertilidad, the Spanish Ministry of Education and Science (TEC2011-29140-C03) and the Generalitat de Catalunya (2009SGR-00282 and 2009SGR-00158). The authors do not have any competing interests.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 20 publications
0
25
0
Order By: Relevance
“…Therefore, a careful approach is required, because no studies with sufficiently long durations have been performed to ensure that there are no effects of electromagnetic waves [15][16][17][18][19]. Recent studies have investigated direct insertions into the zona pellucida and perivitelline space in each embryo using a barcode made of polysilicon with the goal of preventing mix-ups [20][21][22][23][24]. It has been reported that polysilicon barcode tagging can be used to identify individual mouse embryos.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a careful approach is required, because no studies with sufficiently long durations have been performed to ensure that there are no effects of electromagnetic waves [15][16][17][18][19]. Recent studies have investigated direct insertions into the zona pellucida and perivitelline space in each embryo using a barcode made of polysilicon with the goal of preventing mix-ups [20][21][22][23][24]. It has been reported that polysilicon barcode tagging can be used to identify individual mouse embryos.…”
Section: Discussionmentioning
confidence: 99%
“…Another future perspective are silicone barcodes attached to the zona pellucida (Novo et al, 2013(Novo et al, , 2014, or similar embryo-based traceability innovations that, if demonstrated to be harmless, could also suit PGD/PGS cycles. Such technologies can increase safety beyond the level already guaranteed, from a patient-based perspective, by the EWS.…”
Section: Article In Pressmentioning
confidence: 99%
“…20 Thus, in this case we wanted to examine if the silicon nanowires integrated into the microbarcodes follow the same tendency. 20 Thus, in this case we wanted to examine if the silicon nanowires integrated into the microbarcodes follow the same tendency.…”
Section: The Evaluation Of the Embryo In Vitro Developmentmentioning
confidence: 99%
“…Embryos tagged with a single barcode were inspected every 24 h to assess the number of embryos that retained a barcode (retention rate). [16][17][18][19][20] For instance, just by adding 3 barcodes per embryo we can increase the retention rate up to 80% (in the case of the pushpin method). After the initial stage, the retention rate decreased following embryo development (Fig.…”
Section: The Barcode Retention On the Zpmentioning
confidence: 99%
See 1 more Smart Citation